Contemporary selling building relationships, creating value - Johnston, Mark W.; Marshall, Greg W. (Routledge, 2022)
"Contemporary Selling is the only book that combines full coverage of up-to-date personal selling processes with a straightforward look at sales management practices, delivered in a way that students want to learn and instructors want to teach. The overarching theme of the book is enabling salespeople to build relationships successfully and to create value with customers. Johnston and Marshall have created a comprehensive, holistic source of information about the selling function in modern organizations that links the process of selling (what salespeople do) with the process of managing salespeople (what sales managers do). A strong focus on the modern tools of selling, such as customer relationship management (CRM), social media and technology-enabled selling, and sales analytics, means the book continues to set the standard for the most up-to-date and student-friendly selling book on the market today. Pedagogical features include: Update mini cases to engage students and reinforce learning objectives; Ethical Dilemma and Global Connection boxes that simulate real-world challenges faced by salespeople and their managers; Role Play exercises that enable students to learn by doing; and Updated discussion queries to drive classroom discussion and help students connect important concepts. This fully updated new edition is an invaluable resource for students of personal selling at both undergraduate and postgraduate levels. Supplementary resources include an instructor's manual, PowerPoints, and other tools to provide additional support for students and instructors"--